STUDI TENTANG BENTUK MOTIF DAN TEKNIK SULAMAN BAJU PASUMANDAN DI DESA NAREH KOTA PARIAMAN - Dra. Jupriani, M.Sn., SILVIA SUKMA NINGSIH, Dra. Ernis, M.Pd., (Serupa The Journal of Art Education, 2017)
This research was conducted in the village of Nareh, Pariaman. Aim to get information form motifs and embroidery techniques pasumandan shirt. This research is a descriptive qualitative research. Collecting data in this study are primary data is embroidered shirt pasumandan and the craftsmen and secondary data from books and the internet. Research Conclusion: a source of ideas in a dress embroidered pasumandan of flora and geometric shapes. The names of the motifs form Shirt pasumandan bungo roses, jasmine Bungo, Bungo corals, leaf siriah, sidingin leaves, leaves, dankaluak pack, in Sabik, monks and wide swath. Techniques used in embroidery clothes pasumandan them with mechanical engineering manual (skewers straight and zigzag), manually or with a hand such as embroidered in gold thread with stab eel, embroidered sequins (puncture baste, OFF trail and both) and embroidery (straight, zigzag). Pasumandan clothes are clothes worn every woman who became the wife of the oneman.Keyword: form motifs, embroidery techniques, pasumandan shirt.